Response of Robusta Coffee (Coffea canephora.L) Germination Stages That Get Treatment with Long Soaking and Gibberellin Concentration (GA3) - Nelfia Pitri; violita violita (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2022)
Robusta coffee (Coffea canephora L.) is one of the mainstay commodities of plantations in Indonesia. Robusta coffee takes a long time to germinate because Robusta coffee has a hard seed coat so that it is difficult for water and oxygen to penetrate the seed coat which causes the germination process to be hampered. For this reason, it is necessary to speed up germination by stripping the hard seed coat and soaking it with gibberellins. The aim of this study was to obtain the proper concentration of gibberellins and soaking time on the germination of robusta coffee seeds with the husks removed. This research was conducted at the Biology Laboratory, Padang State University in November – January 2022. This study used a completely randomized design (CRD) with two treatment factors. The first factor is the concentration of gibberellins with 3 levels, namely 0, 10, and 20 ppm, the second factor is soaking time with 3 levels, namely 12, 18 and 24 hours. The results showed that the concentration of gibberellins had a significant effect on the parameters of germination height, root length, dry weight, percentage of germination in the early stages of radicle germination and seedling. the duration of immersion and the interaction of the two did not significantly affect the germination rate, vigor index, percentage of germination of seedlings 2 and 3.